Dephosphorylation of the Core Clock Protein KaiC in the Cyanobacterial KaiABC Circadian Oscillator Proceeds via an ATP Synthase Mechanism - Egli, Martin (2012)
The circadian clock of the cyanobacterium Synechococcus elongatus can be reconstituted in vitro from three proteins, KaiA, KaiB and KaiC in the presence of ATP, to tick in a temperature-compensated manner. KaiC, the central cog of this oscillator, forms a homo-hexamer with twelve ATP molecules bound between its N- and C-terminal domains and exhibits unusual properties. Both the N-terminal (CI) and C-terminal (CII) domains harbor ATPase activity and the subunit interfaces between CII domains are the sites of auto-kinase and auto-phosphatase activities. Hydrolysis of ATP correlates with phosphorylation at threonine and serine sites across subunits in an orchestrated manner, such that first T432 and then S431 is phosphorylated, followed by dephosphorylation of these residues in the same order. Although structural work has provided insight into the mechanisms of ATPase and kinase, the location and mechanism of the phosphatase have remained enigmatic. From the available experimental data based on a range of approaches, including KaiC crystal structures and small angle X-ray scattering (SAXS) models, metal ion dependence, site-directed mutagenesis (i.e. E318, the general base) and measurements of the associated clock periods, phosphorylation patterns and dephosphorylation courses as well as a lack of sequence motifs in KaiC that are typically associated with known phosphatases, we hypothesized that KaiCII makes use of the same active site for phosphorylation and dephosphorlyation. We observed that wt-KaiC exhibits an ATP synthase activity that is significantly reduced in the T432A/S431A mutant. We interpret the first observation as evidence that KaiCII is a phospho-transferase instead of a phosphatase and the second that the enzyme is capable of generating ATP, both from ADP + Pi (in a reversal of the ATPase reaction), and ADP + P-T432/P-S431 (dephosphorylation). This new concept regarding the mechanism of dephosphorylation is also supported by strikingly similar make-ups of the active sites at the interfaces between α/β heterodimers of F1-ATPase and between monomeric subunits in the KaiCII hexamer. Several KaiCII residues play a critical role in the relative activities of kinase and ATP synthase, among them R385 that stabilizes the compact form and helps to plateau kinase action and T426, a short-lived phosphorylation site that promotes and affects the order of dephosphorylation.